OPTIMIZATION STRATEGY OF OVERSEAS OPERATION MANAGEMENT OF CHINESE ENTERPRISES BASED ON INTERNATIONAL EXECUTIVE EDUCATION COURSES - Wei, Yu; Waworuntu, Stephanus Remond (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
The purpose of this paper is to explore the challenges and optimization strategies faced by Chinese enterprises in their overseas operations and management processes. Jiangxi ZHENGBANG Plant Protection Co., Ltd, for example, conducts overseas operations mainly in Pakistan, Indonesia, Cambodia, Myanmar, Nigeria and 12 other countries. ZHENGBANG is a national high-tech enterprise focusing on the development, production and sales of pesticide dosage forms, pesticide intermediates and preparations, and is committed to the development of pesticide products for the prevention, elimination or control of agricultural and forestry pests and other pests, including insecticides, fungicides, herbicides and plant regulators. With the in-depth implementation of the "Belt and Road Initiative", Jiangxi ZHENGBANG Plant Protection Co., Ltd. actively expands the international market, and still faces multiple challenges in the field of cross-cultural management and municipal competition strategy, and needs to strengthen human resources and asset allocation management and supply chain digital transformation. In addition, the issue of intellectual property protection and compliance with national laws also needs to be resolved.By analyzing the successful experience of SIEMENS and MAZAK, this paper provides targeted optimization strategies for Chinese enterprises to improve the efficiency and competitiveness of their overseas operations(Dong, et al., 2015). Starting from the actual business background of the company, the research deeply discusses its continuous improvement method through literature review, which provides a solid theoretical basis for analyzing the actual operation status of Chinese enterprises.This study takes the success of SIEMENS and MAZAK as examples to analyze the root causes of the successful experience of their overseas operating companies. Drawing on the successful experience of SIEMENS and MAZAK, this study found a set of innovative optimization strategies aimed at comprehensively improving the efficiency and competitiveness of Chinese enterprises' overseas operations by utilizing advanced technologies and adopting a continuous improvement approach(Ren, 2024).